Landuse Types within Channel Corridor and River Channel Morphology of River Ona, Ibadan, Nigeria - Olutoyin Fashae; Adeyemi Oludapo Olusola (Indonesian Journal of Geography, 2017)
The importance of river a corridor warrants a well thought out and balanced management approach because it helps in improving or maintaining water quality, protecting wetlands, etc. Hence, this study seeks to identify major landuse types within the River Ona Corridor; examine the impact of these landuse types within the River Ona corridor on its channel morphology and understand the risk being posed by these landuse types. The study is designed by selecting two reaches of six times the average width from each of the four major landuse types that exist along the river corridor. This study revealed that along the downstream section of Eleyele Dam of River Ona, natural forest stabilizes river channel banks, thereby presenting a narrow and shallow width and depth respectively but the widest of all is found at the agricultural zones.